2021
DOI: 10.2147/jpr.s293528
|View full text |Cite
|
Sign up to set email alerts
|

Is It Necessary to Approach the Severe Osteoporotic Vertebral Biconcave-Shaped Fracture Bilaterally During the Process of PKP?

Abstract: Purpose The goal of this study was to explore the outcomes of unilateral and bilateral approach percutaneous kyphoplasty (PKP) using CT-guidance in the treatment of severe osteoporotic single-level vertebral biconcave-shaped fracture. Methods We retrospectively reviewed 89 patients with severe osteoporotic single-level vertebral biconcave-shaped fracture who had undergone unilateral and bilateral PKP surgeries using CT-guidance at our hospital between June 2013 and June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Since DSA can be used to assist surgery in different departments, the prevalence of equipment is high. 12 However, PKP treatment of multi-vertebral OVCF has not been reported for the DSA-guided unilateral lateral pedicle approach. Study Suggests unilateral approach percutaneous vertebroplasty is an effective treatment for multiple osteoporotic vertebral compression fractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since DSA can be used to assist surgery in different departments, the prevalence of equipment is high. 12 However, PKP treatment of multi-vertebral OVCF has not been reported for the DSA-guided unilateral lateral pedicle approach. Study Suggests unilateral approach percutaneous vertebroplasty is an effective treatment for multiple osteoporotic vertebral compression fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have demonstrated that DSA-guided surgery can reduce intraoperative fluoroscopy times and radiation injury. 12 , 18 Furthermore, a recent study demonstrated that PKP guided by DSA could reduce the times and doses of fluoroscopy. 19 However, there is no report on the fluoroscopy dose of PKP guided by DSA in treating multi-vertebral osteoporotic fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral PKP is considered the universal approach for the management of OVCF by injecting cement via both pedicles, and one important advantage of this approach is the good distribution of bone cement ( 19 , 24 ). By contrast, bilateral PKP has certain shortcomings, such as higher frequency of intraoperative fluoroscopy and risk of cement leakage ( 25 ). Compared with that in bilateral PKP, unilateral PKP is associated with reduced operation time and risk of puncture, but the disadvantage of uneven distribution of bone cement may lead to vertebral refracture.…”
Section: Discussionmentioning
confidence: 99%
“…Because a successful puncture can not only avoid complications, it also promotes the symmetrical distribution of bone cement after puncture 4 . Although many puncture methods have been designed, including pedicle, paravertebral, anterolateral, and posterolateral approaches, PVA with CTPA under the C-arm is the most commonly used approach 5 6 . A unilateral pedicle approach can meet the surgical requirements at one time, but if the inclination is small, the cement usually deposits on one side of the vertebral body, and there is no force on the opposite side.…”
Section: Introductionmentioning
confidence: 99%